Literary Anamneses. Illnesses and their Textual Beginnings - GLASENAPP, Nicolai (Anafora, 2023)
Literary texts present illnesses as parts of a communicative structure that constitutes illness itself. It remains to prove whether literature takes part in a process that can be described as removal of illness-related taboos or if the specific figuration of literary texts tends to partly relate to the process of tabooing. This paper analyses literary texts by Georg Büchner, Thomas Mann, Gottfried Benn, Franz Kafka, Georg Heym, Alfred Döblin, and David Wagner, and considers their beginnings as a context for the introduction of illness. Special focus is given to what is said and what is unsaid in this context, indicating questions of what is (un)known about illness. The paper focuses on central categories connected with the configuration of illnesses and their textual beginnings: symbolic spaces; causality and destiny; action as illness; illness as an open wound; borders of the body and epistemic closures; setting and suspension of illness as part of interpretation. As a central result, the paper points out that illness does not detach from taboo completely but that it oscillates between tabooing and removal of taboos. In this way, literature tries to present illness as a whole and avoids exaggerating a rational perspective on illness that suppresses important aspects of human subjects, which has massive implications for the linked topics literature, knowledge and illness.